Management of knowledge project - González Amago, Jesús; Marquez de la Calleja, Lourdes; Rabadán López, Beatriz (Conferência - Investigação e Intervenção em Recursos Humanos, 2018)
Leitmotiv of the G.C. of Fundación ONCE: “The knowledge that is not shared does not exist” Origin of the Project: why does it arise? The detection of certain needs in our organization led us to consider how to respond to them: Promote the relationship and communication between Areas and Departments, as a necessary premise to generate a culture oriented to share knowledge within the organization. Improve communication and coordination between the different levels of the organization (technicians, middle managers and managers), to create a deep and efficient knowledge management model. Encourage communication with the outside world, in order to learn from the environment and have knowledge that can be used within the Foundation. Find the levers that motivate our human team, to create an environment conducive to sharing knowledge and experiences among us.